The incidence of Diabetic Cystopathy among Iraqi Diabetic Patients with lower Urinary Tract Symptoms - Saif AM. Abdul-Hameed; Mohammed Bassil Ismail (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Diabetic cystopathy disease is one of the most important problems facing diabetics. Determining theprevalence rate is one of the basics to know the effect of hyperglycemia on bladder patients to provide them withthe best treatment services. And reduce the percentage of damage that occurs to the functioning of the bladderover a duration of disease.Aim of study: identify the prevalence of diabetic cystopathy among diabetic patients.Patients and methods: A cross sectional study were conducted from the first of Jun 2019 to end of December 2020.We selected convenient sample includes all Diabetic patients presenting with voiding dysfunction attending toprivate clinic of Dr. Saif al-haideri for urodynamic study and and who that meeting the eligibility criteria, datacollection by A structured questionnaire is developed to collect information from the participation after physicalexamination and Urodynamic evaluation was done.Result: The total study sample were 550 diabetic patients, out of them 112 (20.4%) were diabetic cystopathy.(56% male and 44% female) with mean age was 56.50±15.50 years. The mean duration of diabetic diagnosis was(13.7±8.25) years with 75% were more than 10 years, while (742.70±158.29 ml) the mean volume of bladder capacityand (87.35±81.82 ml/cm H2O) mean of compliance and without any statically significant association (p=0.120 and0.989 respectively).Conclusion: 20.4% of Iraqi diabetic patients have diabetic cystopathy, and without any statically significantassociation between urodynamic finding and duration of diabetic disease.